THEME: THE SKELETON - Sharobiddinova Lazokatxon O'lmasboy qizi (TADQIQOTLAR, 2025)
The human  skeleton is  the  internal  framework  of  the human  body.  It  is composed of around 270 bones at birth – this total decreases to around 206 bones by adulthood after some bones get fused together. The bone mass in the skeleton makes up about 14% of the total body weight (ca. 10–11 kg for an average person) and reaches maximum mass between the ages of 25 and 30. The human skeleton can be divided into the axial skeleton and the appendicular skeleton. The axial skeleton is formed by the vertebral  column,  the rib  cage,  the skull and  other  associated  bones.  The appendicular  skeleton,  which  is  attached  to  the  axial  skeleton,  is  formed  by the shoulder girdle, the pelvic girdle and the bones of the upper and lower limbs.